Amphetamine Abuse and Intracranial Hemorrhage - J Gordon Millichap (Pediatric Neurology Briefs, 2000)
Eight young adults presenting with intracranial hemorrhage at the Department of Neurosurgery, Queen’s Medical Center and University Hospital, Nottingham, UK, in a 3 and 1/2 year period, were diagnosed with amphetamine abuse.